Rapid identification and preclinical evaluation of new P.vivax vaccine candidates based on alpha helical coiled-coil protein motifs. (2012)
Malaria is one of the most challenging public health problems with 2.5 billion people exposed to the disease in the tropics, and 500 million clinical cases reported yearly worldwide. Plasmodium vivax is responsible for more than 50% of malaria cases outside of Africa, affecting vast areas of Asia and America any others. In Colombia, P. vivax is responsible for >60% of annual malaria cases. Because of limited efforts to develop a vaccine against P.vivax, only a few vaccine candidates have been identified during the last two decades, although the parasite genome contains >5000 genes. To overcome the slow and inefficient malaria vaccine screening system we have been using successfully bioinformatics tools, peptide synthesis and animal preclinical studies to accelerate the discovery/development of new P.falciparum vaccine candidates and propose to conduct similar studies on P. vivax in context of Swiss-Colombian collaboration. Further jusfication of these studies are the recent plans to eradicate malaria worldwide, proposed by WHO and others almost one year ago, where P. vivax is a prime target of roll out of interventions. The goal of this project is the rapid identification and preclinical evaluation of new P.vivax vaccine candidates that could be further assessed in clinical trials. This will be approached by the following specific objectives a) selecting in P.vivax the genome, protein fragments leading to coiled coil structures; b) assessing their antigenicity using reagents from endemic populations; c) evaluating the immunogenicity and protective efficacy in rodents and primates respectively and, d)studying the diversity of selected genes in endemic regions of Colombia & PNG.. The methology to be used consists in an extensive bioinformatics screening of the P. vivax genome data base (PlasmoDB) searching for P.vivax protein sequences from asexual blood stages predicted to contain coiled-coild structures. Selected peptides will be synthesized by Fmoc chemistry, purified by HPLC and analized by Mass Spectrometry (MS) and circular dicroism. Antigenicity of such pepties will be assessed using sera and cells from individuals from malaria endemic regions. Specific IgG (subclasses) will be assessed by ELISA and T-CD4+ cell responses will be assessed by determination of cytokine profiles (Flow cytometry). IgG will be purified by affinity chromatography and used for in vitro erythrocyte invasion inhibition and IFAT assays. Immunogenicity of selected peptides will be tested in BALB/c mice, and their protective efficacy will be determined in immunized Aotus monkey I.V. by challenge with PvSal I parasites by microscopic and PCR follow-up. Genetic diversity will be studied only for promising genes. This 3 year project will be conducted through collaboration between Centro Internacional de Vacunas and the Immunology Institute in Cali-Colombia and the Biochemistry Department at Lausanne University and the Swiss Tropical Institute (Basel) in Switzerland. The project will include a strong technology transfer component through the training of graduate students from both countries. Results are expected to have wide dissemination in the scientific community and will strengthen curricular courses on protein chemistry for graduate and undergraduate students at Universidad del Valle. Studies will not have any negative environmental impact and are expected to have immediate application for vaccine development. Because of the huge disease burden of malaria endemic communities the project has great social relevance.